Artificially Edited Alleles of the Eukaryotic Translation Initiation Factor 4E1 Gene Differentially Reduce Susceptibility to Cucumber Mosaic Virus and Potato Virus Y in Tomato - Atarashi, Hiroki; Jayasinghe, Wikum Harshana; Kwon, Joon; Kim, Hangil; Taninaka, Yosuke; Igarashi, Manabu; Ito, Kotaro; Yamada, Tetsuya; Masuta, Chikara; Nakahara, Kenji S. (Frontiers in Microbiology, 2020)
Eukaryotic translation initiation factors, including eIF4E, are susceptibility factors for viral infection in host plants. Mutation and double-stranded RNA-mediated silencing of tomato eIF4E genes can confer resistance to viruses, particularly members of the Potyvirus genus. Here, we artificially mutated the eIF4E1 gene on chromosome 3 of a commercial cultivar of tomato (Solanum lycopersicum L.) by using CRISPR/Cas9. We obtained three alleles, comprising two deletions of three and nine nucleotides (3DEL and 9DEL) and a single nucleotide insertion (1INS), near regions that encode amino acid residues important for binding to the mRNA 5 cap structure and to eIF4G. Plants homozygous for these alleles were termed 3DEL, 9DEL, and 1INS plants, respectively. In accordance with previous studies, inoculation tests with potato virus Y (PVY; type member of the genus Potyvirus) yielded a significant reduction in susceptibility to the N strain (PVYN), but not to the ordinary strain (PVYO), in 1INS plants. 9DEL among three artificial alleles had a deleterious effect on infection by cucumber mosaic virus (CMV, type member of the genus Cucumovirus). When CMV was mechanically inoculated into tomato plants and viral coat accumulation was measured in the non-inoculated upper leaves, the level of viral coat protein was significantly lower in the 9DEL plants than in the parental cultivar. Tissue blotting of microperforated inoculated leaves of the 9DEL plants revealed significantly fewer infection foci compared with those of the parental cultivar, suggesting that 9DEL negatively affects the initial steps of infection with CMV in a mechanically inoculated leaf. In laboratory tests, viral aphid transmission from an infected susceptible plant to 9DEL plants was reduced compared with the parental control. Although many pathogen resistance genes have been discovered in tomato and its wild relatives, no CMV resistance genes have been used in practice. RNA silencing of eIF4E expression has previously been reported to not affect susceptibility to CMV in tomato. Our findings suggest that artificial gene editing can introduce additional resistance to that achieved with mutagenesis breeding, and that edited eIF4E alleles confer an alternative way to manage CMV in tomato fields.